Excess Blood Flow Response to Acute Resistance Exercise in Individuals Who are Obese or Nonobese. Issue 11 (November 2017) - Lipford, Grayson F.; Evans, Ronald K.; Acevedo, Edmund O.; Wolfe, Luke G.; Franco, R. Lee
Abstract : Abstract: Lipford, GF, Evans, RK, Acevedo, EO, Wolfe, LG, and Franco, RL. Excess blood flow response to acute resistance exercise in individuals who are obese or nonobese. J Strength Cond Res 31(11): 3120–3127, 2017—Resistance exercise (RE) is a commonly recommended treatment option for obese individuals. However, little is known regarding alterations in vasodilatory responses to RE, which could impair exercise tolerance. No studies to date have compared microvascular vasodilatory capacity, assessed by excess blood flow (EBF), responses in individuals who are obese or nonobese following acute RE. The purpose of the study was to evaluate EBF before and up to 24-hour after a single RE bout in obese ( n = 18, 38.1 ± 7.64% body fat) and nonobese ( n = 10, 23.6 ± 4.03% body fat) individuals who volunteered to participate. Each subject completed a leg flexion and knee extension one repetition maximum (1RM) test, and subsequently completed 4 sets of 8 repetitions at 85% of 1RM. Excess blood flow, adiponectin, and tumor necrosis factor α (TNF-α) were evaluated at baseline (PRE-RE), immediately after (POST-RE), and 1 (POST-1) and 24 (POST-24) hours after exercise. A repeated-measures analysis of variance revealed a significant interaction for EBF between the 2 groups ( p = 0.029). The estimated marginal means plot suggested that obese individuals had a significant increase in POST-RE EBF in comparison with PRE-RE EBF (428.54 ± 261.59 vs. 547.00 ± 311.15 ml/100 ml/min·s; p = 0.046). In addition, EBF significantly decreased at POST-24 in comparison with POST-RE in the obese individuals (547.00 ± 311.15 vs. 389.33 ± 252.32 ml/100 ml/min·s; p = 0.011). Changes in EBF were not related to adiponectin or TNF-α. An acute bout of RE resulted in an opposite EBF response between nonobese and obese individuals immediately after RE. Furthermore, only the obese individuals displayed a significant increase in EBF immediately after RE, which was significantly reduced 24 hours after the RE bout. Microvascular vasodilatory capacity may alter the adaptive exercise response associated with RE, requiring alterations to frequency, intensity, and/or duration that are specific to populations of various body composition profiles.